Saving Face: Future Proofing Tāmaki Makaurau Through Facade Adaptions - Bloor, Cosmo (Auckland University of Technology, 2026)
Our daily effect on climate change may feel minute, but when multiplied by eight billion, the results become much more tangible. Inherently the way we live, work and travel is flawed, as cities advance across natural environments, in search of new places for growing populations to live and work. The fabric of our urban environments creates separation between human and non-human communities, impacting historical and cultural spaces. Roads and urban sprawl split environments, reducing natural habitats and dissolving natural systems, while the glass boxes of our skyscrapers create pockets of isolation. A change is needed to reconnect our communities to our culture and history by reconnecting with the landscape, and reintroducing nature into our lives and cities to create holistic regeneration. Our buildings can hold the key to our future through the application of green architecture and passive design principles that can vastly reduce our carbon footprint and improve our resilience to climate change. This evolution in the built environment is beginning to happen, supported by a slow change in mindset brought on by the now relevance of our impact on the world. Companies search for solutions to reduce their carbon footprint, and countries look to create data sets to find answers and solutions to curb the steady rise of our world’s temperature. However, change needs to happen now and at a greater level to address the challenges associated with climate change to provide an immediate solution supported by long term initiatives. Saving Face looks to produce a complex architectural and ecological solution to this problem by producing an immediate and sustainable response to cities impacts on climate change. Through an application of past ecologies in a new vertical streetscape language, a regeneration of Auckland City Tāmaki Makaurau can occur.